2015
DOI: 10.1016/j.jsams.2014.06.011
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between the piriformis muscle, low back pain, lower limb injuries and motor control training among elite football players

Abstract: Hides JA, The relationship between the piriformis muscle, low back pain, lower limb injuries and motor control training among elite football players,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 29 publications
(39 reference statements)
2
27
0
1
Order By: Relevance
“…Anatomically, because the piriformis muscle is pear‐shaped, thickness assessment alone is not sufficient to evaluate changes. Felix reported an increased CSA of the piriformis muscle on MRI in elite football players . We demonstrated that piriformis muscle CSA in PS patients was increased on the symptomatic side according to MRI and US.…”
Section: Discussionmentioning
confidence: 49%
“…Anatomically, because the piriformis muscle is pear‐shaped, thickness assessment alone is not sufficient to evaluate changes. Felix reported an increased CSA of the piriformis muscle on MRI in elite football players . We demonstrated that piriformis muscle CSA in PS patients was increased on the symptomatic side according to MRI and US.…”
Section: Discussionmentioning
confidence: 49%
“…The final study found that cross sectional area (CSA) of the piriformis muscle was similar in football players with and without current LBP but the typical piriformis adaptation to increased physical demands during the season was affected negatively by LBP. In addition, the risk of sustaining lower limb injuries during the season was significantly higher in the players with smaller piriformis CSA (15).…”
Section: Resultsmentioning
confidence: 92%
“…Three MRI studies, all performed by the same research group, measuring the thickness of the abdominal and pelvic muscles were eligible (13)(14)(15). Hides et al (2010) compared the ability of 43 elite male Australian football players with and without LBP from a single club to contract the abdominal wall.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations